Reshape of the HR practices due to the COVID-19 pandemic - Šimonová, Berta; Pauknerová, Daniela, 1970-; Mura, Ladislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The COVID-19 has shaken all enterprises, creating a complex and challenging environment for employees, managers, and human resources management (HRM), who must find solutions to ensure business continuity and deal with the global economic crisis. There are few studies on the impact of COVID-19 on the workplace. The theoretical section of the thesis tries to increase understanding and scope concerning the employment conditions influenced by the pandemic’s dilemma. It analyzes the most significant difficulties associated with pandemic and workplace transformation, as well as insights for company management and HR department into various approaches, as well as acceptance of hybrid workplaces and other atypical types of employment. The goal is to analyze the impact of the COVID-19 pandemic on the HR practices that were being implemented before and observe how they changed. This Master's Thesis will examine how the pandemic altered the HR procedures of one of the construction firms. The technique comprises of in-depth interviews with eight HR representatives from a single organization. All of the questions answered in these interviews focused on the most essential HR tasks hit by the pandemic, including working conditions, staffing, performance management, training and career development, compensation management, and health and safety management. In addition, the interviewed HR representatives discussed the future opportunities brought about by the pandemic, as well as new initiatives that would be implemented in the near future. The findings demonstrate a successful way for a corporation to handle a crisis. It also demonstrates the significance of things such as trust in making the corporation stronger
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses